IMPLEMENTASI PENGELOLAAN DANA DESA BERDASARKAN PERATURAN BUPATI NOMOR 25 TAHUN 2016 TENTANG TATA CARA PEMBAGIAN DAN PENETAPAN RINCIAN DANA DESA SETIAP DESA SERTA PETUNJUK TEKNIS PENGGUNAAN DANA DESA TAHUN ANGGARAN 2016 (Studi Kasus di Desa Dawung Kecamatan Matesih Kabupaten Karanganyar) - Damayanti Suhita, Cindiyana Anggraini, Joko Pramono & (Transformasi, 2017)
The village of Dawung has been a success implementing use of a village Fund phase oneprocess so that its success can be a guidance or inspiration to other villages. This research aimsto provide an overview of the implementation of the village Fund (DD) for infrastructuredevelopment and community empowerment in the village of Dawung sub-district of MatesihKaranganyar Regency. Analysis showed that the implementation of the management of thevillage Fund based on the regulations of Regent number 25 year 2016 is already going prettywell.Key words: Public Policy, Implementation, The Village Fund